Effect of exposure to active allethrin on expression of HSF2 and Ovol1 genes in a rat spermatogenesis - Sagita, Retno Putri; Rasyid, Rosfita; Ali, Hirowati (International Journal of Research in Medical Sciences, 2019)
Background: Heat shock factor protein 2 (HSF 2) and Ovo like transcriptional repressor 1 (Ovol1) genes are found in germ cells that control spermatogenesis. One reason is exposure to mosquito repellent drugs from allethrin. Allethrin is one of the causes of male reproductive dysfunction that affects male reproduction resulting in infertility. Methods: This study was an experimental post-test randomized control group design. Twenty-eight rats given exposure according to the experimental group were K (control), P1 (4 hours exposure), P2 (8hours exposure), and P3 (12hours exposure) for 30 days. Examination of HSF 2 and Ovol1 genes from testicular tissue using real-time PCR with a relatively quantitative calculation method. Implementation of research at animal houses and biomedical laboratories. Data analysis using one-way ANOVA with a significant level of p <0.05. Results: The results of this study found differences in the average number of expressions of the HSF2 and Ovol1 genes. The average expression of the HSF2 control group gene was 3.50, P1: 2.99, P2: 0.62, and P3: 0.49. Whereas in the Ovol1 gene control group were 1.17, P1: 0.80, P2: 0.57, and P3: 0.65. The results of statistical tests using one-way ANOVA are HSF2 (p = 0,000) and Ovol1 (p = 0.045). Conclusions: Based on the results of this study, it was concluded that there was an allethrin effect in decreasing the expression of the HSF 2 and Ovol1 genes in Wistar albino Rattus Novergicus strain.